Номер 13

Доведіть нерівність:

1) 2a – 3 < 2(a – 1);
2a – 3 – 2(a – 1) = 2a – 3 – 2a + 2 = 1 < 0, тому 2a – 3 < 2(a – 1);

2) c(c + 2) > c2 + 2c – 3;
c(c + 2) – (c2 + 2c – 3) = c2 + 2cc2 – 2c + 3 = 3 > 0, тому c(c + 2) > c2 + 2c – 3;

3) (x + 2)(x – 2) + 5 > x2;
(x + 2)(– 2) + 5 – x2 = x2 – 4 + 5 – x2 = 5 – 4 = 1 > 0, тому (x + 2)(x – 2) + 5 > x2;

4) 3m – 2 < m(m + 3);
3m – 2 – m(m + 3) = 3m – 2 – m2 – 3m = –m2 – 2 = –(m2 + 2).
Оскільки m2 ≥ 0 за будь-якого значення m, то m2 + 2 > 0, –(m2 + 2) < 0.
Отже, 3m – 2 < m(m + 3).